2016
DOI: 10.15252/embj.201693929
|View full text |Cite|
|
Sign up to set email alerts
|

The hVps34‐ SGK 3 pathway alleviates sustained PI3K/Akt inhibition by stimulating mTORC 1 and tumour growth

Abstract: We explore mechanisms that enable cancer cells to tolerate PI3K or Akt inhibitors. Prolonged treatment of breast cancer cells with PI3K or Akt inhibitors leads to increased expression and activation of a kinase termed SGK3 that is related to Akt. Under these conditions, SGK3 is controlled by hVps34 that generates PtdIns(3)P, which binds to the PX domain of SGK3 promoting phosphorylation and activation by its upstream PDK1 activator. Furthermore, under conditions of prolonged PI3K/Akt pathway inhibition, SGK3 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
124
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(135 citation statements)
references
References 62 publications
(95 reference statements)
9
124
2
Order By: Relevance
“…The almost undetectable expression of Sgk2 suggests that this isoform is unlikely to play a critical role in the control of thyroid cell proliferation. On the other hand, Sgk3 is unique among the SGK genes, since it has a N-terminal PX-domain targeting the protein to the endosomes, where it is activated in response to the class III PI3K Vps34 (23). Based on these notions, as well as on preliminary shRNA-based experiments showing very limited effects of Sgk3 depletion on cell proliferation (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…The almost undetectable expression of Sgk2 suggests that this isoform is unlikely to play a critical role in the control of thyroid cell proliferation. On the other hand, Sgk3 is unique among the SGK genes, since it has a N-terminal PX-domain targeting the protein to the endosomes, where it is activated in response to the class III PI3K Vps34 (23). Based on these notions, as well as on preliminary shRNA-based experiments showing very limited effects of Sgk3 depletion on cell proliferation (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of 18 biopsies from patients treated with alpelisib showed that samples with high SGK1 mRNA and phospho-N-Myc downstream regulated 1 (NDRG1; a substrate for and biomarker of SGK1 activation) levels correlated with intrinsic resistance to alpelisib, whereas most phospho-NDRG1-negative tumors were from patients who attained partial responses or stable disease. Similarly, SGK3 overexpression and/or activation has been repeatedly linked to PI3K/mTOR inhibitor resistance in breast cancer cells (Bago et al, 2016; Gasser et al, 2014). These reports offer a common mechanism for intrinsic or acquired resistance to PI3K or AKT inhibitors.…”
Section: Therapeutic Targeting Of the Pi3k Pathway In Cancermentioning
confidence: 99%
“…SGK3 has been shown to play a pivotal role in Akt-independent signaling downstream of oncogenic PIK3CA mutations in some human cancers, including breast cancer (11). Most recently, Bago et al reported that SGK3 counteracts the inhibition of PI3K/Akt signaling and stimulates tumor growth (12). SGK3 is amplified and hyperactivated in breast cancer (13), and its expression is regulated by ERα and positively correlates with ERα levels in breast tumors (14,15).…”
mentioning
confidence: 99%